Analisis Determinan Massa Otot Lansia di Panti Bhakti Kasih Siti Anna Kota Pangkalpinang - Ratmawati, Ratmawati; Emilia, Emilia (Journal of Nutrition College, 2021)
Background: The Central Bureau of Statistics Republic of Indonesia (2019) stated that the percentage of elderly in Indonesia reached 9.60% (25.64 million), in 2017 proportion of elderly (> 60 years) in Bangka Belitung was 6.31% and 6.38% in Pangkalpinang City. The prevalence of sarcopenia of elderly in Indonesia is quite high (40.6%). Sarcopenia is affected by age, gender, nutritional status, physical activity, protein intake, vitamin D, chronic disease, and genetics.Objectives: To analyze the determinant of muscle mass (nutritional status, vitamin D intake, and duration of sun exposure) of elderly at Panti Bhakti Kasih Siti Anna Pangkalpinang City.Methods: The quantitative observational study, with a cross sectional design and conducted at Panti Bhakti Kasih Siti Anna Pangkalpinang City, in 2020. The sample of study was elderly at Panti Bhakti Kasih Siti Anna who met the inclusion and exclusion criteria of 22 people. Methods of measurement muscle mass used BIA, nutritional status used anthropometry, research questionnaire to determine characteristics of respondents and duration of sun exposure, vitamin D intake by the SQ-FFQ instrument.Results: The average of muscle mass elderly was 35.1 kg with the muscle mass index was 16.7 kg/m2. There were correlated nutritional status, intake of vitamin D, and duration of sun exposure with muscle mass index of elderly (p < 0.05).Conclusion: Multivariate analysis stated that nutritional status can be used to predict the incidence of sarcopenia based on muscle mass index of elderly with correlation was -0.455 and an opposite correlation.